Effect of Hydraulic Retention Time on MES Operation for Biomethane Production - Nelabhotla, Anirudh B. T.; Khoshbakhtian, Mahdi; Chopra, Neha; Dinamarca, Carlos (Frontiers in Energy Research, 2020)
Hydraulic retention time (HRT) is one of the most important factors to be analyzed and optimized in continuous flow operations such as the integrated process of microbial electrosynthesis system (MES) and anaerobic digestion (AD). Highest methane production rate of 12.2 ± 0.1 mmol/L(feed)-d was obtained at 18-h HRT with reject water feed that was supplemented with acetic acid. Highest amount of COD removal of 23.4% was obtained at 18-h HRT operation with the reject water feed that was not supplemented with acetic acid. The pH of the effluent was 8.63 and 7.64 at 18-h HRT for both the feed types, respectively. This resulted in net alkalinity reduction implying conversion of bicarbonate to methane at 90% of biogas. It was also observed that the electrochemical methane production rates were higher in feeds that were not supplemented with acetic acid along with additional COD degradation via direct electro-oxidation of organics at anode.